Narasi Bāb al-‘Ilm: Kontekstualisasi Ali bin Abi Thalib dalam Periwayatan Hadis dan Pembentukan Tradisi Intelektual Islam - Ach Badri Amien; Widayatul Amalia (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
Ali ibn Abi Talib was known as a figure with a breadth of knowledge so that the Prophet called himself the city of knowledge, while Ali was called its gate. However, in the narration of hadith, Ali's contribution is relatively small compared to other companions such as Abu Hurairah or Anas ibn Malik. This condition raises academic questions that become a research gap because previous studies only highlight aspects of Ali's leadership and knowledge in general, without specifically examining the relationship between the title of bāb al-‘Ilm and the limited narration of hadith and its implications for the formation of Islamic civilization. This study aims to explain the reasons why the Prophet called Ali the gate of knowledge, analyze the factors that led to the small number of hadith he narrated, and trace the influence of his knowledge on the development of Islamic intellectualism. The approach used is descriptive qualitative through a literature study sourced from classical works and modern scientific literature. The findings of this study indicate that the title of bāb al-‘Ilm reflects Ali's spiritual and intellectual depth, while his careful narration of hadith is related to his commitment to maintaining the authenticity of the Prophet's words. On the other hand, his contributions to Islamic civilization are evident in laying the foundations of the science of grammar, strengthening the tradition of interpretation, and early theological-philosophical thought in Islam. Thus, this study provides novel value in understanding Ali ibn Abi Talib's intellectual position as a narrator and early architect of the Islamic scientific tradition.